2013
DOI: 10.1155/2013/306705
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Ellagic Acid on Cell Growth of Ovarian Carcinoma Cells

Abstract: Ellagic acid (EA) is able to inhibit the growth of several cancer cells; however, its effect on human ovarian carcinoma cells has not yet been investigated. Ovarian carcinoma ES-2 and PA-1 cells were treated with EA (10~100 μM) and assessed for viability, cell cycle, apoptosis, anoikis, autophagy, and chemosensitivity to doxorubicin and their molecular mechanisms. EA inhibited cell proliferation in a dose- and time-dependent manner by arresting both cell lines at the G1 phase of the cell cycle, which were from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 27 publications
3
53
1
Order By: Relevance
“…Mitotic arrest can cause the accumulation of P53 [29], and in particular P53 phosphorylated at serine 15 has been reported to induce apoptosis partly via activation of Bax [30]. While P53 expression was increased by carboplatin, KPYB10602 caused little increase of P53 in the present study (data not shown).…”
Section: Discussioncontrasting
confidence: 45%
“…Mitotic arrest can cause the accumulation of P53 [29], and in particular P53 phosphorylated at serine 15 has been reported to induce apoptosis partly via activation of Bax [30]. While P53 expression was increased by carboplatin, KPYB10602 caused little increase of P53 in the present study (data not shown).…”
Section: Discussioncontrasting
confidence: 45%
“…EA exerts its beneficial effects by regulating multiple pathways including: (i) activation of the antioxidant response through the nuclear erythroid 2-related factor 2 (Nrf2) [73,74]; (ii) inhibition of proinflammatory agents, such as cyclooxygenase (COX-2) and cytokines by nuclear factor-kappa B (NF-B) [51,75]; (iii) alteration of several growth factors expression, as the platelet-derived growth factor (PDGF), transforming growth factor beta (TGF-␤), hepatic growth factor (HGF) [76,77]; (iv) depletion of adhesion molecules, like vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) among others [78]; (v) modulation of several cell survival/cell-cycle genes such as cyclin D1 and E, p21, B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein (Bax) [79,80], tumor suppressors (p53, DUSP6, Fos), oncogenes (K-Ras, c-Myc) [81]; (vi) regulation of kinases, like mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3-K), glycogen synthase kinase 3 beta (GSK-3␤) [82][83][84] (Fig. 2).…”
Section: Molecular Targetsmentioning
confidence: 99%
“…In this respect, EA has shown chemopreventive effects in rodent models of oral [105,289,290], esophagic [291,292], mammary [293,294], lung [295], prostatic [296], intestinal [297] and colon cancer [298,299]. Besides, the antiproliferative activity of both EA and urolithins on several tumor cell lines has been clearly demonstrated Table 3 [79,[300][301][302][303]. In contrast, the evidence of anti-hepatocarcinogenic effects of EA is still contradictory (Table 3).…”
Section: Hepatocellular Carcinoma (Hcc) Is a Malignant Tumor Arising mentioning
confidence: 99%
“…For the most part, in nature, they exist as complexes called ellagitannins, which usually undergo hydrolysis in the gastrointestinal tract to form ellagic acid [178]. In vitro and in vivo studies have shown ellagic acid to exert antidiarrheal [179], anti-diabetic [180], anti-carcinogenic [181, 182], anti-inflammatory [183] properties.…”
Section: Pkc Modulation By Polyphenolsmentioning
confidence: 99%